If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20 + -3y = 2 + 9y Solving -20 + -3y = 2 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. -20 + -3y + -9y = 2 + 9y + -9y Combine like terms: -3y + -9y = -12y -20 + -12y = 2 + 9y + -9y Combine like terms: 9y + -9y = 0 -20 + -12y = 2 + 0 -20 + -12y = 2 Add '20' to each side of the equation. -20 + 20 + -12y = 2 + 20 Combine like terms: -20 + 20 = 0 0 + -12y = 2 + 20 -12y = 2 + 20 Combine like terms: 2 + 20 = 22 -12y = 22 Divide each side by '-12'. y = -1.833333333 Simplifying y = -1.833333333
| -24=-3(x-6) | | 9(x-3)=6(x+4) | | 2m-3=m+5 | | 5u^4-30u^3+70u^2=14 | | (2m^2-4)(2m^2+4)= | | 5x+(-7)+2x=21 | | 3(4z-8)-20= | | 2x-17=25-5x | | 42a^2-29a-5= | | 6x-8=-3(4-2x) | | 5u^4-30u^3+70u^2= | | 3X-2=24X+12 | | 6(4-x)=36 | | -6(5a+6b)= | | 3x(14y+19)= | | x+.75=12.25 | | 0=-n-4n | | 6g-3=-19 | | 19-2(2w+1)=11w-2(11+w) | | -4x+2x=x | | 3y+4=2y+1 | | 3[7-(9x-8)]+3x=0 | | -6r+7+1=3r-8r | | (4x+4)(4x-4)= | | y=4x+15 | | 4x^2+27x+77= | | 11=4(x-2)-(x-7) | | 630-540= | | -7x-12=6x+14 | | 5x-(4x+5)=3x-31 | | 8r-6r=2r+3 | | 3(x^2)+5x=50 |